PERLINDUNGAN HUKUM PASIEN DALAM LAYANAN KONSULTASI KESEHATAN ONLINE - Rani Tiyas Budiyanti; Penggalih Mahardika Herlambang (Masyarakat Hukum Kesehatan Indonesia, 2021)
Online medical consultation or often known as teleconsultation is part of telemedicine. The technology began to develop in Indonesia in line with the development of information technology. Flexibility of time, lower consultation costs, wide coverage, and improved health services are the benefits gained from implementing the technology. Nevertheless, the implementation of online medical consultation has potency to create ethical and legal issues in Indonesia such as legality of healthcare, legality of practice licenses, therapeutic transactions, and the issue of confidentiality and security of patient data. Indonesia does not yet have a specific regulation on the implementation of online doctor consultations. Regulations are required for the implementation of online medical consultation so that not to conflict with ethics and law. In addition, information technology in the health sector should be developed to support the implementation of online medical consultation services.